Assessment of chloride natural background levels by applying statistical approaches. Analyses of European coastal aquifers in different environments. (January 2022) - Pulido-Velazquez, D.; Baena-Ruiz, L.; Fernandes, J.; Arnó, G.; Hinsby, K.; Voutchkova, D.D.; Hansen, B.; Retike, I.; Bikše, J.; Collados-Lara, A.J.; Camps, V.; Morel, I.; et al.
Abstract: Estimated natural background levels (NBLs) are needed to assess groundwater chemical status according to the EU Groundwater Directive. They are commonly derived for different substances by applying statistical methodologies. Due to the complexity of the sea water intrusion process, some of those methods do not always provide appropriate assessment of chloride NBLs. This paper analyzes the applicability of different NBL estimation methods in five EU coastal aquifers with significant differences in available datasets and hydrogeological settings. A sensitivity analysis of results to different constraints was performed to remove samples with anthropogenic impacts. A novel statistical approach combining different methods to identify the range of chloride NBLs is proposed. In all pilots the estimated NBLs were below 85 mg/L and fitted well with previous studies and expert judgment, except Campina del Faro aquifer (the maximum being 167.5 mg/L). Although this approach is more time consuming, it provides a more robust solution. Highlights: Natural background levels (NBL) is used for assessing groundwater chemical status. Estimating Cl-NBL is difficult due to the complexity of sea water intrusion process. Existing statistical approaches & hypothesis to assess Cl- NBL are not always valid. A novel statistical approach to identify range of Cl- NBL is proposed and tested. The solution provides more robust results in coastal aquifers across Europe.